The prevention and punishment of crime - Molony, Thomas F., Sir (Statistical and Social Inquiry Society of Ireland, 1923)
I have chosen as the subject of my address "The Prevention and Punishment of Crime," because it is one of interest, not only to lawyers and statisticians, but to every person who loves his country and would like to see it better and happier than it is.
Read January 13th, 1921.
Keywords: Criminal law; Crime prevention; 314.15